Local well-posedness for 2D incompressible magneto-micropolar boundary layer system. Issue 1 (2nd January 2021) - Lin, Xueyun; Zhang, Ting
Abstract : In this paper, we consider the 2D magneto-micropolar boundary layer system. Using a suitable change of variables and performing analytic energy estimates in the tangential variable, we obtain the local well-posedness for the 2D magneto-micropolar boundary layer system when the initial data are analytic in the x variable.